TINGKAT KEPUASAN MAHASISWA TERHADAP LAYANAN AKADEMIK DOSEN PENDIDIKAN AGAMA ISLAM (PENELITIAN PADA MAHASISWA SEMESTER II FAKULTAS ILMU PENDIDIKAN UNIVERSITAS NEGERI SEMARANG) - Ilyas, Ilyas (Universitas Negeri Semarang, 2014)
One of the subjects who had a goal guarding behavior in the learning process of students on campus is MKU (General Courses). And one of the common subjects are Islamic Education (PAI). With subjects such PAI sincerely hope college students to be able to color the character better. Hope is certainly not to blame, but please note that in the process of PAI college is not easy to carry out the mandate in order to make students become better morals. Because the process involves a lot of things, as in educational theory that there are several factors that affect learning, including students, teachers, objectives, content, and the environment. The results of this study indicate that some of the services that it is considered satisfactory academic student in university classes FIP UNNES PAI is mastery of the material by lecturers and professors appearance and acceptance of lecturers to students. Services that still needs improvement is the presence of a lecturer at the college, faculty understanding of the condition of the course students conformity with the plan of activities, evaluation and feedback, availability syllabus and plan learning activities and the provision of reference books.